2019
DOI: 10.1063/1.5081891
|View full text |Cite
|
Sign up to set email alerts
|

Nanotriangle-based gap-enhanced Raman tags for bioimaging and photothermal therapy

Abstract: Surface-enhanced Raman scattering (SERS) nanoparticles can be utilized as optical labeling nanoprobes for bioimaging with advantages of the fingerprint vibrational signal as a unique optical code and the ultra-narrow linewidth for multiplexing. As a new type of SERS nanoprobes, gap-enhanced Raman tags (GERTs) developed recently can overcome the common issues of poor photostability and limited Raman enhancement. In this work, we have constructed bright nanotriangle-based GERTs (NT-GERTs) for combined SERS bioim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It has been shown recently that the location of RMs in ultrasmall gaps rather than near particle tips resulted in a higher SERS signal . Following this strategy, a novel type of label called gap-enhanced Raman tags (GERTs) has been suggested and studied. A typical GERT is composed of a plasmonic Au core with adsorbed RMs and an additional Au shell. For example, GERTs with embedded 1,4-benzenedithiol molecules between the core and a smooth external shell have been developed. , Such nanoparticles demonstrate high and uniform SERS response which make them suitable candidates for cell imaging, in vivo cancer , and lymph node imaging, Raman-guided locoregional plasmonic photothermal therapy, ,, and other applications. , …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown recently that the location of RMs in ultrasmall gaps rather than near particle tips resulted in a higher SERS signal . Following this strategy, a novel type of label called gap-enhanced Raman tags (GERTs) has been suggested and studied. A typical GERT is composed of a plasmonic Au core with adsorbed RMs and an additional Au shell. For example, GERTs with embedded 1,4-benzenedithiol molecules between the core and a smooth external shell have been developed. , Such nanoparticles demonstrate high and uniform SERS response which make them suitable candidates for cell imaging, in vivo cancer , and lymph node imaging, Raman-guided locoregional plasmonic photothermal therapy, ,, and other applications. , …”
Section: Introductionmentioning
confidence: 99%
“…The development of GERTs was initiated by Lim et al, who showed that DNA embedded between a Au core and Au shell provides stable and enhanced SERS signals . This was followed by more experimental and theoretical studies, which were summarized in a recent review by Khlebtsov et al We have recently investigated the optimal design of GERT using Au@SiO 2 @Au with the overall NP size in the range of 35–70 nm, a gap range of 2.5–15 nm, and shell thickness from 2.5 to 10 nm . The optical response of such Au@SiO 2 @Au always consists of two peaks, with one at shorter wavelength that can be attributed to the nonbonding mode largely coming from the Au-core and another one at longer wavelength red-shifted from the nonbonding peak.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Raman nanotags can unexpectedly interact inside biological environments and are also susceptible to photobleaching, which can occur with improper storage or from prolonged exposure to a light source. Recently, a new type of SERS nanotag has emerged called gap-enhanced Raman tags (GERTs), offering a visible improvement in signal intensity through electromagnetic field enhancement. In GERTs, a hard plasmonic shell is synthesized over the Raman-tagged plasmonic structures, which prevents the Raman reporters from leaking. Additionally, the plasmonic shell shields the reporters against unwanted matrix interactions and also protects against photobleaching, therefore ensuring highly stable SERS NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have sought to use thermoplasmonics for a wide variety of applications. These applications include photovoltaics [51,52], liquid heating [53,54], gene therapy [55], thermal biology [56], photothermal cancer therapy [57][58][59][60], imaging and spectroscopy [61,62], and plasmofluidics [63,64]. Some of the thermoplasmonic studies have used the thermally caused shift in the LSPR as a mechanism of temperature sensing [65], whereas Jackman et al [66] devised a highly sensitive method using LSPR that analyzes the deformation in the shape of the protein molecule as it is adsorbs on a metal surface at different temperatures.…”
Section: Introductionmentioning
confidence: 99%